Hospitalizations of the elderly for reasons related to human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) infection, Rondônia, Brazil, 2010–2018 - Burgarelli, Welliton Repiso; Serigiolli, Luan Acas; Marmentini, Gabriel Pandolfo; Gomes, Luciano Teixeira; Fontes, Cor Jesus Fernandes (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: For the elderly, cultural factors and social paradigms predispose to the rejection of condom use, which favors human immunodeficiency virus (HIV) transmission. The North region was the last area for the spread of HIV in Brazil. Rondônia, although with a slight decline in the HIV detection rate in recent years, is still among the states with high mortality rate due to HIV/acquired immunodeficiency syndrome (AIDS) in Brazil. Objective: To describe the demographic and clinical characteristics of the elderly patients who were hospitalized for reasons related to HIV infection in the state of Rondônia, Brazil. Methods: Descriptive study of secondary data recorded from 2010 to 2018. The cause of hospitalization was identified in the field referring to the main and secondary diagnoses of the hospitalization authorization form. Results: Between 2010 and 2018, Rondônia recorded 1,073,932 hospitalizations for any cause in the state’s public hospitals. Out of these, 183,803 (17.1%) were of elderly patients over 60 years of age and 249 (0.13%) were due to HIV/AIDS. There was a progressive increase in the number of hospitalizations during the study period, as well as a predominance of younger elderly men (67.1±6.0 years old). The mean length of hospitalizations was 21.3±21.1 days and 57 (24.1%) elderly patients died. Conclusion: Despite all the progress made in HIV prevention and treatment, the state of Rondônia still has a progressive increase in hospitalizations of elderly people for reasons related to HIV/ AIDS. HIV transmission prevention strategies should be emphasized in the elderly population in the state.